\[\boxed{\text{613\ (613).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[(2n + 1)^{2} + \left( 2n^{2} + 2n \right)^{2} =\]
\[= \left( 2n^{2} + 2n + 1 \right)^{2}\]
\[4n^{2} + 4n + 1 + 4n^{4} + 8n^{3} + 4n^{2} =\]
\[= 4n^{4} + 4n^{2} + 1 + 8n^{3} + 4n^{2} + 4n\]
\[4n^{4} + 8n^{3} + 8n^{2} + 4n + 1 =\]
\[= 4n^{4} + 8n³ + 8n² + 4n + 1\]
\[\boxed{\text{613.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ a + c.\]
\[2)\ m - n.\]
\[3)\ (x + y) \cdot (x - y).\]
\[4)\ (x - y)^{2}.\]
\[5)\ x^{2} - y^{2}\text{.\ }\]